ESTETIKA FILM ANIMASI WOLFWALKERS - Putra, Wayan Vicky Darish; Widagdo, I Gusti Komang Gede Arno; Febrio, Ida Bagus Kevin; Nugraha, I Kadek Rama Ardi; Artha, I Gede Agus Indra Bayu (Anima Rupa, 2023)
Wolfwakers animated film aesthetics. The purpose of this research as intended is: What makes wolfwalkers animation unique, Knowing the aesthetic elements of unity, balance, and emphasis in the Wolfwalkers animated film.This study uses a qualitative method, which collects data from observing films. Observation results from the wolfwalkers animation show that the aesthetic element is very prominent in each image due to its unique visual style, such as the use of hand-drawn techniques (manual animation with paper and pencil) as well as the use of several colors in making backgrounds which are made manually using paint.